2004
DOI: 10.1017/s0025315404010367h
|View full text |Cite
|
Sign up to set email alerts
|

A new species of amphipod crustacean, Pleusymtes comitari sp. nov., associated with gorgonians on deep-water coral reefs off Ireland

Abstract: A new species of pleustid amphipod of the genus Pleusymtes is described from the west coast of Ireland. It was found to be common in association with an Acanthogorgia sp. gorgonian at 725 and 900 m depth on coral habitats in the continental shelf-break areas of the Porcupine Seabight and Porcupine Bank. It is assumed to be a commensal due to its modified pereopod dactyls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…However, the depth at which the peak in diversity is reached varies tremendously and also depends on the taxa investigated. found that, for polychaetes, the highest number of species was seen between 1400-1800 m along the Hebridean Slope, NE Atlantic, whilst Cosson-Sarradin et al (1998) saw a parabolic shaped curve in polychaete diversity with depth in the tropical NE Atlantic, with the maximum occurring at a depth of 2000 m. Gage et al (2000) found that macrofaunal diversity peaked at about 1400 m along the Scottish continental slope, although in the Faroe-Shetland Channel, the genus-level diversity maximum occurs at depths between 450 and 550 m (Bett, 2001;Narayanaswamy et al, 2005Narayanaswamy et al, , 2010. To confuse the issue, bivalves (Allen and Sanders, 1996) and gastropods (Rex et al, 1997) have a variety of patterns in the different basins of the South and North Atlantic.…”
Section: One Of the Highest Diversities On The Planetmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the depth at which the peak in diversity is reached varies tremendously and also depends on the taxa investigated. found that, for polychaetes, the highest number of species was seen between 1400-1800 m along the Hebridean Slope, NE Atlantic, whilst Cosson-Sarradin et al (1998) saw a parabolic shaped curve in polychaete diversity with depth in the tropical NE Atlantic, with the maximum occurring at a depth of 2000 m. Gage et al (2000) found that macrofaunal diversity peaked at about 1400 m along the Scottish continental slope, although in the Faroe-Shetland Channel, the genus-level diversity maximum occurs at depths between 450 and 550 m (Bett, 2001;Narayanaswamy et al, 2005Narayanaswamy et al, , 2010. To confuse the issue, bivalves (Allen and Sanders, 1996) and gastropods (Rex et al, 1997) have a variety of patterns in the different basins of the South and North Atlantic.…”
Section: One Of the Highest Diversities On The Planetmentioning
confidence: 95%
“…(Hovland, 2008;Roberts et al, 2006Roberts et al, , 2008. Although the inventory is ever growing, currently over 1300 species have been reported from cold-water coral reefs, some of which are new to science (Myers and Hall-Spencer, 2004;Mortensen and Fosså, 2006;Henry and Roberts, 2007;Guerra-Garcia, 2008). There are also biogeogrpahic variations in the species found associated to Lophelia and an overall biodiversity decrease from south to north (Hall-Spencer et al, 2002Roberts et al, 2008).…”
Section: Lophelia Reefs: Hot Spots Of Diversitymentioning
confidence: 99%
“…(Hovland, 2008;Roberts et al, 2006Roberts et al, , 2008. Although the inventory is ever growing, currently over 1300 species have been reported from cold-water coral reefs, some of which are new to science (Myers and Hall-Spencer, 2004;Mortensen and Fosså, 2006;Henry and Roberts, 2007;Guerra-Garcia, 2008). There are also biogeogrpahic variations in the species found associated to Lophelia and an overall biodiversity decrease from south to north (Hall-Spencer et al, 2002, 2007Roberts et al, 2008).…”
Section: Lophelia Reefs: Hot Spots Of Diversitymentioning
confidence: 99%
“…These areas usually provide a complex structural habitat supporting a diverse associated fauna (Henry & Roberts, ), and so are recognized as biodiversity hotspots (Hovland, ). Although the inventory is continually growing, currently more than 1300 species have been reported from CWC reefs and colonies (Guerra‐García, Sorbe, & Frutos, ; Henry & Roberts, ; Mortensen & Fosså, ; Myers & Hall‐Spencer, ). In the Mediterranean, the CWC province of S. Maria di Leuca (Ionian Sea, southern Mediterranean) is reported to host more than 250 accompanying species (D'Onghia et al, ; Mastrototaro et al, ).…”
Section: Introductionmentioning
confidence: 99%